Varieties of civil society across Asia - Ogawa, Akihiro 1968-; Spires, Anthony J. 1970- (Routledge, 2025)
"This book explores civil societies with distinct characteristics in Asian countries and regions to redefine the dynamic and interconnected formation that is Asia. This book documents how civil society organizations, such as charities and foundations, across Asia which have traditionally been observed to imitate or borrow the methods employed by Western nongovernmental organizations, have been developing distinctive relations with the state, inventing novel civic techniques. Furthermore, it highlights how such organizations have created a characteristic framework for governance and spaces for new social practices and reflections. Reflecting on the historical backgrounds, political systems, and cultural settings, each case study reveals the diverse and alternative approaches and solutions to various issues facing contemporary Asian society. Studying the dynamism of Asia to highlight the emergence of new civil society practices this book will be a great interest to scholars and students of Asian Studies, Anthropology, Sociology & Political Science"
Keywords: Zivilgesellschaft; Asien; Civil society / Asia; Political participation / Asia; Asia / Politics and government / 21st century; Konferenzschrift -- 2022